Effect of Addition Retention Bead and Repair Material on Transverse Strength of Repaired Acrylic Denture Resin - Majeed, alaa (Iraqi National Journal of Nursing Specialties, 2010)
Objective: One of the most important practical deficiencies of present denture base materials is fracture, therefore many attempts have been made to reinforce of the repaired denture base resin. A desirable objective for this service is to obtain optimum strength for repairs, which can be achieved by making available a good bond between original and repaired materials. Methodology: The present study was carried out to evaluate and compare the transverse strength of acrylic specimens repaired by two different materials (hot-cure and cold-cure acrylic resin). A total of 50 specimens were prepared by hot (40) repair: (10) by hot with retention bead, (10) by cold with retention bead and (10) repair by hot only, (10) repair by cold only, and (10) un repair control made from hot cure acrylic resin. Transverse strength was measured for each specimen using three points bending on a brinell transverse testing machine. Results: The result showed that the repair with heat-cure acrylic resin with retention bead has a significant higher than the repair with cold-cure acrylic resin with retention bead and higher than control specimen (unrepaired). Recommendations: It can be concluded that the hot acrylic resin with retention bead are an important parameter in the reinforcement of repaired acrylic denture base resin.